Identification of Genomic Associations for Adult Plant Resistance in the Background of Popular South Asian Wheat Cultivar, PBW343 - Li, Huihui; Singh, Sukhwinder; Bhavani, Sridhar; Singh, Ravi P.; Sehgal, Deepmala; Basnet, Bhoja R.; Vikram, Prashant; Burgueno-Ferreira, Juan; Huerta-Espino, Julio (Frontiers in Plant Science, 2016)
Rusts, a fungal disease as old as its host plant wheat, an enemy as old as wheat, has caused havoc for over 8,000 years. As the rust pathogens can evolve into new virulent races which quickly defeat to qualitative or vertical the resistance that primarily rely on race specificity over time, adult plant resistance (APR) has often been found to be race non-specific and hence is considered have been proven to be a more to be a more reliable and durable strategy to combat this malady. Over decades sets of donor lines have been identified at International Maize and Wheat Improvement Center (CIMMYT) representing a wide range of APR sources in wheat. In this study, using nine donors and a common parent ‘PBW343’, a popular Green Revolution variety at CIMMYT, the nested association mapping (NAM) population of 1122 lines was constructed to understand the APR genetics underlying these founder lines. Thirty-four QTL were associated with APR to rusts, and 20 of 34 QTL had pleiotropic effects on SR, YR and LR resistance. Three chromosomal regions, associated with known APR genes (Sr58/Yr29/Lr46, Sr2/Yr30/Lr27, and Sr57/Yr18/Lr34), were also identified, 13 previously reported QTL regions were validated. Of the 18 QTL first detected in this study, 7 were pleiotropic QTL, distributing on chromosomes 3A, 3B, 6B, 3D, and 6D. The present investigation revealed the genetic relationship of historical APR donor lines, the novel knowledge on APR, as well as the new analytical methodologies to facilitate the applications of NAM design in crop genetics. Results shown in this study will aid the parental selection for hybridization in wheat breeding, and envision the future rust management breeding for addressing potential threat to wheat production and food security.